Minocycline Treatment Reverses Sound Evoked EEG Abnormalities in a Mouse Model of Fragile X Syndrome - Lovelace, Jonathan W.; Ethell, Iryna M.; Binder, Devin K.; Razak, Khaleel A. (Frontiers in Neuroscience, 2020)
Fragile X Syndrome (FXS) is a leading known genetic cause of autism with symptoms that include intellectual disability, anxiety, social impairments and sensory hypersensitivity deficits. Electroencephalogram (EEG) recordings from humans with FXS and an animal model, the Fmr1 knockout (KO) mouse, show remarkably similar phenotypes suggesting that EEG phenotypes can serve as biomarkers for developing treatments. This includes enhanced resting gamma band power and sound evoked total power, and reduced fidelity of temporal processing and habituation of responses to repeated sounds. Given the therapeutic potential of the antibiotic minocycline in humans with FXS and animal models, it is important to determine sensitivity and selectivity of EEG responses to minocycline. Therefore, in this study, we examined if a 10-day treatment of adult Fmr1 KO mice with minocycline (oral gavage, 30 mg/kg per day) would reduce EEG abnormalities. We tested if minocycline treatment has specific effects based on the EEG measurement type (e.g., resting versus sound-evoked) and cortical region (auditory versus frontal) in the Fmr1 KO mice. Minocycline treatment increased gamma band phase locking to auditory stimuli, and reduced sound-evoked power of auditory event related potentials (ERP) in Fmr1 KO mice compared to vehicle treatment. Reduced resting gamma band power was observed in Fmr1 KO mice following minocycline treatment, but this effect was similar to vehicle treatment. We also report cortical region and frequency specific effects on EEG responses, with more robust changes in the frontal cortex. Taken together, these data indicate that sound-evoked EEG responses may serve as more sensitive measures, compared to resting EEG measures, to isolate minocycline effects from placebo in FXS. Given the use of minocycline and EEG recordings in a number of neurodegenerative and neurodevelopmental conditions, these findings may be more broadly applicable in translational neuroscience.